2016
DOI: 10.3399/bjgp16x688369
|View full text |Cite
|
Sign up to set email alerts
|

Secondary prevention lifestyle interventions initiated within 90 days after TIA or ‘minor’ stroke: a systematic review and meta-analysis of rehabilitation programmes

Abstract: BackgroundStrokes are often preceded by a transient ischaemic attack (TIA) or ‘minor’ stroke. The immediate period after a TIA/minor stroke is a crucial time to initiate secondary prevention. However, the optimal approach to prevention, including non-pharmacological measures, after TIA is not clear.AimTo systematically review evidence about the effectiveness of delivering secondary prevention, with lifestyle interventions, in comprehensive rehabilitation programmes, initiated within 90 days of a TIA/minor stro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 36 publications
0
22
0
2
Order By: Relevance
“…140 Similar results have been reported in patients recovering from TIA. 141 In ambulatory exercise-based cardiac rehabilitation, a detailed pre-participation screening is important to rule out or treat risk factors for recurrent TIA or stroke. In this regard, patients should undergo clinical evaluation by a healthcare professional with expertise in stroke care to determine risk for recurrent stroke and initiate appropriate investigations and management strategies.…”
Section: History Of Transient Ischaemic Attack/strokementioning
confidence: 99%
“…140 Similar results have been reported in patients recovering from TIA. 141 In ambulatory exercise-based cardiac rehabilitation, a detailed pre-participation screening is important to rule out or treat risk factors for recurrent TIA or stroke. In this regard, patients should undergo clinical evaluation by a healthcare professional with expertise in stroke care to determine risk for recurrent stroke and initiate appropriate investigations and management strategies.…”
Section: History Of Transient Ischaemic Attack/strokementioning
confidence: 99%
“…Studies have shown that higher levels of total bilirubin are associated with lower risk of asymptomatic cerebral infarction. [24] Tan et al [17]also proved that total bilirubin can be used as an independent risk factor for MIS. Indeed, as nomogram shows, it is reasonable that higher levels of bilirubin can prevent the recurrence of cerebral infarction to some extent.…”
Section: Discussionmentioning
confidence: 99%
“…Stable vital signs, clear consciousness; (4). Unilateral upper limb Brunnstrom evaluation: I-IV period; (5) Age from 20 to 80 years old; (6) The course of the diseases from 2 weeks to 6 months. The exclusion criteria for this study included the following: (1) A history of epilepsy; (2) Function failure in important organs such as heart, lung, liver, kidney, etc.…”
Section: Participantsmentioning
confidence: 99%
“…Motor dysfunction after stroke leads to a heavy financial pressure on the families. Post-stroke hemiplegic rehabilitation includes early rehabilitation treatment [2], routine treatment [3], computer aided rehabilitation training [4], secondary prevention by improving the life style [5], transcranial direct current stimulation [6], scalp acupuncture (SA) [7,8], repetitive transcranial magnetic stimulation (rTMS) [9] and other interventions. When traditional Chi-nese treatment is combined with Western medicine rehabilitation therapy, it is more common that SA [10,11] and rTMS are used in hemiplegia rehabilitation after stroke.…”
Section: Introductionmentioning
confidence: 99%